2015
DOI: 10.2147/ndt.s92968
|View full text |Cite
|
Sign up to set email alerts
|

Altered intrinsic regional spontaneous brain activity in patients with optic neuritis: a resting-state functional magnetic resonance imaging study

Abstract: ObjectiveTo investigate the underlying regional homogeneity (ReHo) in brain-activity deficit in patients with optic neuritis (ON) and its relationship with behavioral performance.Materials and methodsIn total, twelve patients with ON (four males and eight females) and twelve (four males and eight females) age-, sex-, and education-matched healthy controls underwent resting-state functional magnetic resonance imaging scans. The ReHo method was used to assess the local features of spontaneous brain activity. Cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
49
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 51 publications
(54 reference statements)
3
49
0
Order By: Relevance
“…The 240 functional images were analyzed as described previously. 17 Briefly, the data were filtered by MRIcro (Nottingham University, Nottingham, UK) and preprocessed using SPM8 (The MathWorks, Inc., Natick, MA, US) and DPARSFA (Institute of Psychology, CAS., Beijing, People’s Republic of China) software. Then, the data were processed with slice timing, head motion correction, spatial normalization, and smoothening with a Gaussian kernel of 6×6×6 mm 3 full-width at half-maximum (FWHM).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The 240 functional images were analyzed as described previously. 17 Briefly, the data were filtered by MRIcro (Nottingham University, Nottingham, UK) and preprocessed using SPM8 (The MathWorks, Inc., Natick, MA, US) and DPARSFA (Institute of Psychology, CAS., Beijing, People’s Republic of China) software. Then, the data were processed with slice timing, head motion correction, spatial normalization, and smoothening with a Gaussian kernel of 6×6×6 mm 3 full-width at half-maximum (FWHM).…”
Section: Methodsmentioning
confidence: 99%
“…Based on Kendall’s coefficient of concordance (KCC), ReHo computation was performed with the REST software (Center for Cognition and Brain Disorders, HZNU., Hangzhou, Zhejiang, People’s Republic of China), as previously described. 17 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Diffusion tensor imaging (DTI) is an extension of DWI that can be utilized to assess the integrity of the white matter of the optic nerve in vivo by using tractography related to specific white matter tracts [24]. Fractional anisotropy [25] ranging from 0.0 to 1.0 is a commonly used parameter that reflects the consistency of water molecules in the direction of motion in a voxel, which is altered by the integrity of the structure and the consistency of the arrangement of fiber bunches [26]. The higher 1 3…”
Section: Tips Pertaining To Pathophysiological Informationmentioning
confidence: 99%
“…Blood oxygenation level-dependent functional MRI can depict cerebral cortex activity using blood flow information. Shao [25] reported that ON involved the defaultmode network on resting-state functional magnetic resonance imaging. Huang [35] came to a similar conclusion using amplitude of low-frequency fluctuation.…”
Section: Tips Pertaining To Pathophysiological Informationmentioning
confidence: 99%